Process modeling applied to the improvement of management of a Civil Engineering Model Office (Research, Society and Development, 2019)
The process vision can help in the management of organizations of different sizes and different areas of activity, mainly due to the potential of representation that process modeling has. Based on the process view, this paper presents a process improvement proposal from the Model Office of Civil Engineering of the Federal University of Pampa. This is a qualitative case study research in which the BPMN notation was used to model the current state of the office processes studied. With this, we aimed to identify points of improvement, which were later represented in the modeling of the future state of the processes. As a result it was found that the improvement points identified in the studied processes are related to project management solutions. These data indicate the possibility of using project management software and the need for project management training. The study indicates that process modeling can be used in relatively simple and informal processes to help improve the management of small organizations.